2008
DOI: 10.1111/j.1365-2672.2007.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various environmental factors on the viability of Cryptosporidium parvum oocysts

Abstract: Aims:  To evaluate individual and combined effects of temperature (4, 18 and 25°C), pH (7 and 10), ammonia (5 and 50 mg l−1) and exposure time (1, 2, 4 and 6 days) on the viability of Cryptosporidium parvum oocysts in water. Methods and Results:  The viability of oocysts was evaluated using the fluorogenic vital dyes assay (4′,6‐diamidino‐2‐phenylindole and propidium iodide). All the factors analysed (temperature, pH, ammonia and exposure time) and their interaction were statistically significant (P < 0·005). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
(56 reference statements)
2
15
0
3
Order By: Relevance
“…The die-off rate for oocysts in river water at 5°C is similar to that in autoclaved river water, but at 15°C, oocyst die-off occurs more rapidly in natural than in autoclaved river water (27). The difference is perhaps due to increased biological or biochemical activity at 15°C, as suggested by the authors of the study (27 (19,20,30,(32)(33)(34)(35)(36), in vitro excystation (40), and cell culture (25,28). …”
Section: Oocyst Survival In Watermentioning
confidence: 50%
See 1 more Smart Citation
“…The die-off rate for oocysts in river water at 5°C is similar to that in autoclaved river water, but at 15°C, oocyst die-off occurs more rapidly in natural than in autoclaved river water (27). The difference is perhaps due to increased biological or biochemical activity at 15°C, as suggested by the authors of the study (27 (19,20,30,(32)(33)(34)(35)(36), in vitro excystation (40), and cell culture (25,28). …”
Section: Oocyst Survival In Watermentioning
confidence: 50%
“…The lowest K value occurred at 4°C, which agrees with the findings of Walker and Stedinger (38), who stated that the mortality rate of oocysts increases as the temperature increases above 4°C. For 4°C, the mean of collated K values was 0.0086 day Ϫ1 , with the values ranging from 0.0029 day Ϫ1 up to 0.0272 day Ϫ1 (19,20,30,(32)(33)(34)(35)(36)40). With increases in temperature up to 37°C, K increased exponentially.…”
Section: Oocyst Survival In Watermentioning
confidence: 99%
“…ensure a high level of environmental contamination and increase the likelihood of waterborne transmission. Firstly, they are responsible for disease in a broad range of hosts including man [9, 10], have a low-infectious dose (10–30 oocysts) enhancing the possibility of infection also in healthy immunocompetent people [11, 12], which may shed 10 8 -10 9 oocysts in a single bowel movement and excrete oocysts for up to 50 days after cessation of diarrhea [13, 14]; secondly, their transmissive stages (oocysts) are small in size and environmentally robust [15, 16] and thirdly, they are insensitive to the normal disinfectants commonly used in the water industry [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings further support the hypothesis that the presence of one or more environmental factors may prevent contaminated water reaching the shellfish farm area and contaminating molluscs (Giangaspero et al 2009). et al 1989;Johnson et al 1997;Lim et al 1999;Olson et al 1999;Nasser et al 2003, Reinoso et al 2008. In fact, the ability of Cryptosporidium oocysts to initiate infection has been linked to finite carbohydrate energy reserves in the form of amylopectin, consumed in direct response to ambient temperatures (Fayer et al 1998b).…”
Section: Discussionmentioning
confidence: 97%
“…Fayer et al (1996b) reported that oocysts were totally inactivated when exposed to an atmosphere of pure ammonia at 21 and 23°C for 24 h. Jenkins et al (1998) showed that 24-h exposure to a concentration of 1,020 mg NH 3 per litre inactivated 64.5% of C. parvum oocysts. Reinoso et al (2008) reported that C. parvum oocyst viability following 4 days' exposure to 5 and 50 mg NH 3 per litre was 41.5 and 14.8%, respectively. Increasing the ammonia concentration and exposure time increased the inactivation of C. parvum oocysts.…”
Section: Ammonia Concentrationmentioning
confidence: 98%